H-Infinity Controller Based on LMI Region for Flexible Robot Manipulator - Mohd Zaidi, Mohd Tumari; Muhammad Salihin, Saealal; Mohd Riduwan, Ghazali; Mohd Anwar, Zawawi; L. H., Shah (MedWell, Journal, 2012)
This study presents investigations into the development of H-infinity controller with LMI region schemes for trajectory tracking and vibration control of a Flexible Robot Manipulator System. A constrained planar single-link flexible manipulator is considered and the dynamic model of the system is derived using the assume mode method. H-infinity synthesis with pole clustering schemes is used to control the hub angle with very minimal vibration at the end-point of the manipulator. The performance of the flexible robot manipulator system is examined in terms of time response specifications of hub angle, minimal vibration at the end-point of the manipulator and minimal control input torque. To examine the effectiveness of the proposed controller, it is compared with hybrid input shaping with collocated PD controller schemes. The implementation results show that H-infinity controller with confined closed-loop poles based on LMI region produce a fast tracking capability with very minimal end-point vibration and smooth control input torque.